Castells in Africa Universities and Development - Muller, Johan; Cloete, Nico; van Schalkwyk, Francois (African Minds, 2016)
Castells in Africa: Universities and Development collects the papers produced by Manuel Castells on his visits to South Africa, and publishes them in a single volume for the first time. The book also publishes a series of empirically-based papers which together display the multi-faceted and far-sighted scope of his theoretical framework, and its fecundity for fine-grained, detailed empirical investigations on universities and development in Africa. Castells, in his afterword to this book, always looking forward, assesses the role of the university in the wake of the upheavals to the global economic order. He decides the university's function not only remains, but is more important than ever. This book will serve as an introduction to the relevance of his work for higher education in Africa for postgraduate students, reflective practitioners and researchers.